Analisis Pengaruh Campuran Pelumas Tellus 32 Dan Minyak Kelapa Sawit Dengan Pelumas Tellus 32 Terhadap Total Acid Number Dan Viscositas - Nugraha, Aldi; Ariyanto, Ariyanto; Sateria, Angga (Jurnal Inovasi Teknologi Terapan, 2023)
Lubricants are chemical substances that are generally in liquid form, which are used in frictional components. Its function is to reduce friction, reduce wear, reduce vibration, maintain the age of the tool or component and maintain temperature during operation. The purpose of this study was to determine the effect of a mixture of lubricants on TAN (Total Acid Number) and viscosity, and to determine the effect of time on TAN (Total Acid Number) and viscosity. It was carried out with 5 different concentrations of the mixture, namely 100:0, 80:20, 90:10, 95:5, 0:100 then the concentration of this mixture was tested on the headstock gearbox of a conventional lathe DoALL LT 13 for 21 hours at each concentration, then the test is carried out on the lubricant sample repeated 3 times every 1 hour. The viscosity test on lubricating oil samples was carried out at 40°C and the TAN (Total Acid Number) test was carried out at room temperature. This research was conducted using the ANOVA method and it was concluded that the analysis showed that mixing and time had a significant effect on TAN (Total Acid Number) and viscosity.